Organizational cluster-based aspect of reviving and developing railway tourism - Сіваконева, Ганна Олександрівна; Балака, Євгеній Іванович (Technology audit and production reserves, 2014)
The organizational aspect of a railway tourism revival in Ukraine was considered. For its development, a cluster approach was proposed. It was found that the development of railway tourism in modern conditions is impossible without diversifying railway transport activities into the adjacent segment of economy management, i.e. tourism. It was suggested carrying out the diversification by developing transport and tourism clusters. The purpose of creating the transport and tourism cluster lies in increasing the competitiveness of railway transport and tourism market by means of a synergetic effect, the efficiency improvement of enterprises and organizations, belonging to the cluster, innovation promotions and development of new activities. Carrying out tourist activities by Ukrainian railways as a tour operator requires a long-term railway tourism program, which will involve asystem of management and organizational solutions, include meeting population’s needs in tourist services, create a positive image of the railways in a tourism market by providing competitive advantages of railway transport in the passenger transportation market and taking into account an environmental influence and inner potential of railways.